2006
DOI: 10.1002/jmor.10469
|View full text |Cite
|
Sign up to set email alerts
|

Surface ciliation of anuran amphibian larvae: Persistence to late stages in some species but not others

Abstract: Scanning electron microscopy was used to examine the surfaces of 21 species of tadpoles from six families, from Gosner Stage 25/26 until close to metamorphosis. Contrary to most previous reports, ciliated epidermal cells persisted until late stages in many but not all species and not at all locations examined. The commonest location for ciliated cells was around the nostrils, suggesting a role in chemosensation. Ciliated cells also occurred around the circumference of the eye, suggesting a cleaning role. Sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 13 publications
0
17
0
Order By: Relevance
“…However, the cilia are gradually lost and so is their characteristic morphology (Nishikawa and Sasaki ; Nokhbatolfoghahai et al . ). In Rhinella granulose , the ciliated cells were observed until stage 31.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, the cilia are gradually lost and so is their characteristic morphology (Nishikawa and Sasaki ; Nokhbatolfoghahai et al . ). In Rhinella granulose , the ciliated cells were observed until stage 31.…”
Section: Discussionmentioning
confidence: 97%
“…These cells are also involved in cutaneous respiration by providing more oxygenated water currents (Fox ; Nokhbatolfoghahai et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…Both ciliary action and muscular contraction induce intra ovum convective mixing (Warkentin 2007;Goldberg et al 2008). Epidermal cilia serve many roles before and after hatching, including the movement of mucus, microorganisms, and debris, rotations before hatching and gliding movements after hatching, and water-quality assessment, as well as disruption of boundary layers to improve gas exchange (Burggren 1985;Doran et al 2004;Nokhbatolfoghahai et al 2005) (Nokhbatolfoghahai et al 2005(Nokhbatolfoghahai et al , 2006. In fact, the number of surface cilia increases with development until the embryo approaches hatching (Kessel et al 1974).…”
Section: Introductionmentioning
confidence: 99%
“…The ciliated cells gradually begin to disappear around Stage 14. Nokhbatolfoghahai et al (2006) investigated 20 species of anurans, including a direct-developing frog Pristimantis urichi, and concluded that the cilia are an ancestral larval feature that persists in direct-developing frogs. Richardson et al (1998) reported the presence of ciliated cells in E. coqui from Stage 4 onward, but provided no details.…”
Section: Endolymphatic Calcium Deposits and Ciliated Cells In A Maramentioning
confidence: 99%
“…Hayes et al (2007) identified ciliated cells, goblet cells that produce mucus, and small secretory cells of unknown function in the epidermis of X. laevis. Nokhbatolfoghahai et al (2006) investigated 20 species of anurans, including a direct-developing frog Pristimantis urichi, and concluded that the cilia are an ancestral larval feature that persists in direct-developing frogs. These authors suggested that ciliated cells might function to prevent the retention of microorganisms and cell debris on the epidermis of the embryo; for P. urichi, they described the presence of large numbers of ciliated cells in the pharyngeal region and on the tail fins, which are structures associated with respiration, as is the tail of A. maranguapensis.…”
Section: Endolymphatic Calcium Deposits and Ciliated Cells In A Maramentioning
confidence: 99%